2013
DOI: 10.1177/1359105312470156
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing two approaches to weight loss: Differences in weight loss maintenance

Abstract: This study compared treatment outcomes for a new weight loss program that emphasized reducing unhealthy relationships with food, body image dissatisfaction, and internalized weight bias (New Perspectives) to a weight loss program that emphasizes environmental modification and habit formation and disruption (Transforming Your Life). Fifty-nine overweight and obese adults (body mass index ≥ 27 kg/m2) were randomly assigned to either a 12-week New Perspectives or Transforming Your Life intervention. Despite equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 41 publications
1
77
0
1
Order By: Relevance
“…Preliminary evidence suggests that including components of treatment to address weight stigma with patients may facilitate positive treatment outcomes [55] including weight loss [56]. In light of documented associations between weight stigmatization and binge eating, increased food consumption, and reduced physical activity, all of which can reinforce weight gain and interfere with weight loss, identifying that effects of stigma on body weight seem particularly warranted.…”
Section: Weight Gain Obesity and Weight Lossmentioning
confidence: 98%
“…Preliminary evidence suggests that including components of treatment to address weight stigma with patients may facilitate positive treatment outcomes [55] including weight loss [56]. In light of documented associations between weight stigmatization and binge eating, increased food consumption, and reduced physical activity, all of which can reinforce weight gain and interfere with weight loss, identifying that effects of stigma on body weight seem particularly warranted.…”
Section: Weight Gain Obesity and Weight Lossmentioning
confidence: 98%
“…Similar interventions have also yielded positive weight (Anglin, 2012;Gagnon-Girouard et al, 2010;Lillis, Hayes, Bunting, & Masuda, 2009;Rapoport, Clark, & Wardle, 2000;Tanco, Linden, & Earle, 1998), fitness (Carrier, Steinhardt, & Bowman, 1994) and psychological outcomes (Ciliska, 1998;Gagnon-Girouard et al, 2010;Lillis et al, 2009;Omichinksi & Harrison, 1995;Tanco et al, 1998). However, some interventions that target weight stigma have found no significant benefits, such as one that targeted internalized weight bias, which found no benefit over an environmental modification and habit formation disruption intervention (Carels et al, 2014), and some longitudinal studies found that higher weight stigma is associated with better weight loss outcomes (e.g., Latner, Wilson, Jackson, & Stunkard, 2009). Yet other interventions are currently being conducted, and their results when available will also inform intervention efforts (e.g., Tirlea, Truby, & Haines, 2013).…”
Section: Model Summary and Future Researchmentioning
confidence: 99%
“…Self-monitoring data were obtained from 89 participants enrolled in two similar BWLPs (Study 1: N = 45; [18]; Study 2: N = 44; [19]). Data were used from two similar studies to increase statistical power.…”
Section: Participantsmentioning
confidence: 99%